2012
DOI: 10.1177/193229681200600218
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Glucose Meter with a Built-in Automated Bolus Calculator versus Manual Bolus Calculation in Insulin-Using Subjects

Abstract: Insulin-using patients made errors in more than half of the manually calculated insulin doses. Use of the automated bolus calculator in the FreeStyle InsuLinx meter minimized errors in dose determination. The patients also expressed confidence and preference for using the meter. This may increase adherence and help optimize the use of mealtime insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 8 publications
1
75
0
Order By: Relevance
“…Sussman and colleagues documented the numeracy problem in a study that found that patients made errors 63% of the time in calculation of their correction bolus dose and/or their prandial carbohydrate-based dose when provided with the standard formulae. 18 In that study, the use of a BC improved the accuracy of the insulin dose to over 90%. At this time, there are 84 BCs that are downloadable from iTunes for use on smart phones.…”
Section: Bolus Calculators (Bc)mentioning
confidence: 96%
“…Sussman and colleagues documented the numeracy problem in a study that found that patients made errors 63% of the time in calculation of their correction bolus dose and/or their prandial carbohydrate-based dose when provided with the standard formulae. 18 In that study, the use of a BC improved the accuracy of the insulin dose to over 90%. At this time, there are 84 BCs that are downloadable from iTunes for use on smart phones.…”
Section: Bolus Calculators (Bc)mentioning
confidence: 96%
“…Such calculators already exist for bolus insulin (primarily for insulin pumps or intensive care units), and several studies on such devices or programs have been published. [61][62][63][64][65][66][67][68][69][70] It is imaginable that the availability of basal insulin dose calculators that incorporate basal insulin titration algorithms-under the condition that the previously mentioned issues are taken into accountassists patients and physicians in real life and leads to substantial improvements of diabetes control. This improvement of diabetes control should be proven in controlled trials.…”
Section: What Are the Future Perspectives?mentioning
confidence: 99%
“…1 There is also an increasing body of evidence that bolus calculators may improve glycemic control and treatment satisfaction in patients who use these devices as intended.…”
Section: Potential Benefitsmentioning
confidence: 99%